A Controversial Parable – The Vineyard Tenants (Mt 20:1-16) - Kustár, György (Booklets of Sárospatak, 2024)
We always take risk when we analyse biblical texts in order to reach its original setting and message. But this endeavour can be fruitful, as the problems surrounding the tenant worker’s parable clearly demonstrates. The interpretations of the church – throughout her whole history – unfortunatelly covered the scandal in this piece of artwork, and the problem of unjust payment has been explained as „radical grace”, as the result of the first worker’s laziness, bad attitude or the diligence of the latecomers. These misinterpretations do not make justice to the text. No explanation can cast shadow on the visible moral dilemma. The grapeyard owner throught Mediterranian eyes does not deserve sympathy, his deed cannot be excused. We got used to look at this story from the viewpoint of the last hired laborers. We are thankful for such a grace – but the parable forces us into the role of the first workers, who legitimately protest against the disproportionate wage. Only through our indignation, dispise, annoyment can we arrive to the real understanding, accepting that we would never act like the owner, that according to our measures and ideals this act is a scandal. Only after this confession can we arrive to the last workers – and to the undeserved and disturbing grace.
Keywords: tenant workers; radical grace; parable; scandal; teaching of the historical Jesus